The Effectiveness of Kinesiotaping, Sham Taping or Exercises Only in Lateral Epicondylitis Treatment: A Randomized Controlled Study - AKYÜZ, GÜLSEREN DERYA (WILEY, 2019)
Background: Lateral epicondylitis is a common musculoskeletal condition presenting with pain and tenderness over the lateral epicondyle and dorsal forearm, pain and weakness in gripping and limitations in daily activities. It is proposed that kinesiotaping, a new application of adhesive taping, reduces pain and improves muscle function. Objective: To compare efficacy of kinesiotaping, sham taping, or exercises only in the treatment of lateral epicondylitis. Design: Double-blind, randomized, controlled trial. Setting: Tertiary medical center, university hospital. Participants: Thirty patients with lateral epicondylitis for less than 12weeks. Methods or Interventions: Patients were randomized into three groups: kinesiotaping plus exercises (n = 10), sham taping plus exercises (n = 10), and control (exercises only) (n = 10) groups. All recipients were provided a home exercise program including strengthening and stretching exercises. In kinesiotaping and sham taping groups, tapings were performed and changed every 3-4 d for 2 weeks. Main Outcome Measure(s): The primary outcome was the patient-rated tennis elbow evaluation (PRTEE). Pain visual analogue scale (VAS), grip strength, and the disabilities of the arm, shoulder and hand (QuickDASH) scales were secondary outcomes. Evaluations were done at baseline, posttreatment, and at 4 weeks after treatment. The immediate effect was also assessed by VAS and grip strength immediately after real and sham tapings. Results: PRTEE total scores at posttreatment and at 4 weeks after treatment were statistically significantly lower in kinesiotaping plus exercises group compared to sham taping plus exercises group and exercises only group. The effects of kinesiotaping were larger than sham taping and only exercises at posttreatment (d = -1.21, d = -1.33) and at 4 weeks after treatment (d = -1.39, d = -1.34). Repeated-measures anova showed a significant interaction between the time and the groups (F 2950 = 4849; P = .006). Significant between-group differences were found in QuickDASH score and VAS at rest at 4 weeks after treatment, VAS at daily activity at posttreatment and 4 weeks after treatment when kinesiotaping plus exercises and sham taping plus exercises groups and kinesiotaping plus exercises and exercises only groups were compared. Real taping but not sham taping immediately led to an increase in grip strength, decrease in VAS at rest and VAS at daily activity (P = .0017, P = .041, P = .028; respectively). Conclusions: Kinesiotaping in addition to exercises is more effective than sham taping and exercises only in improving pain in daily activities and arm disability due to lateral epicondylitis.
Keywords: ELASTIC THERAPEUTIC TAPE; ELBOW TENDINOPATHY; BOTULINUM TOXIN; IMPROVE PAIN; MANAGEMENT; INJECTION; FUNCTIONALITY; STRENGTH